2023
DOI: 10.1021/acs.jcim.3c00310
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Dynamics Simulation-Driven Focused Virtual Screening and Experimental Validation of Inhibitors for MTDH-SND1 Protein–Protein Interaction

Abstract: Protein–protein interactions (PPIs), in general, are attractive yet challenging drug targets. As a typical PPI, MTDH-SND1 interaction has recently been reported to be a promising drug target to malignant breast cancer and other cancer types. However, the lack of well-defined deep pockets on the MTDH-SND1 interface makes it a tough target for rational drug discovery attempts. To address this issue, in this study, a long time-scale molecular dynamics (MD) simulation-driven focused screening strategy was proposed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 74 publications
(139 reference statements)
0
1
0
Order By: Relevance
“…The entropy contribution was not considered in this study as adding the entropy contribution may lead to additional errors. This setup has been used successfully to characterize the potential binding mode of the ligand on different protein–ligand systems in our previous studies. …”
Section: Methodsmentioning
confidence: 99%
“…The entropy contribution was not considered in this study as adding the entropy contribution may lead to additional errors. This setup has been used successfully to characterize the potential binding mode of the ligand on different protein–ligand systems in our previous studies. …”
Section: Methodsmentioning
confidence: 99%
“…Changing the linkage position of the amine and substituting the N atom of the triazolopyridine in the B fragment simultaneously results in a significant decrease in inhibition activity, suggesting that the linkage mode between the A and B fragments and the alpha N of the triazolopyridine may be important structural affecting the binding of small molecule inhibitors to SND1. Although no direct hydrogen bond between the sulfonamide group and the SND1 pocket was observed from the co-crystal structure, Xu et al suggested that the sulfonamide group, rather than the methyltriazolopyridinamine part, might form a hydrogen bond with SND1 R255 based on molecular dynamics simulation study of C26-A6 132 . The reports of compound C26 series as well as two SND1 co-crystals validate the hydrophobic pocket in the MTDH-SND1 complex with potential binding ability to small molecule inhibitors.…”
Section: Small-molecule Inhibitorsmentioning
confidence: 99%
“…Based on the discovery of C26 series molecules and the evaluation of anti-tumor activity, Xu et al discovered 7 small molecules that could bind to SND1 protein with KD value less than 15μM from 1.2 million molecules by molecular docking and various molecular dynamics simulations 132 . Among them, compound L5 had an IC50 value of 57 μM for MDA-MB-231 cell proliferation and immunofluorescence (IF) assay verified that L5 inhibited the PPI of MTDH-SND1 in cells.…”
Section: Small-molecule Inhibitorsmentioning
confidence: 99%
See 1 more Smart Citation